Commercial Interests in Continuing Medical Education: Where Do Electronic Health Record Vendors Fit?. (November 2020) - Rubinstein, Pesha F.; Middleton, Blackford; Goodman, Kenneth W.; Lehmann, Christoph U.
Abstract : The Accreditation Council for Continuing Medical Education (ACCME) will not accredit an organization that it defines as a commercial interest, that is an entity that produces, markets, resells, or distributes health care goods or services consumed by, or used on, patients. Thus, commercial interests are not eligible to be accredited organizations offering continuing medical education (CME) credit to physicians. This decision is based on the concern that commercial interests may use CME events to market their products or services to physicians, who then might inappropriately prescribe or administer those products or services to patients. Studies have shown that CME events supported by pharmaceutical companies, for example, have influenced physicians' prescribing behaviors. Currently, however, the ACCME does not recognize electronic health record (EHR) vendors, which are part of a multi-billion-dollar business, as commercial interests, and it accredits them to provide or directly influence CME events. Like pharmaceutical company-sponsored CME events, EHR vendor activities, which inherently only focus on use of the sponsoring vendor's EHR system despite its potential intrinsic limitations, can lead to physician reciprocity. Such events also may inappropriately influence EHR system purchases, upgrades, and implementation decisions. These actions can negatively influence patient safety and care. Thus, the authors of this Perspective call on the ACCME to recognize EHR vendors as commercial interests and remove them from the list of accredited CME providers.